Effectiveness of Ethics & Compliance Work : Nordic Compliance Officers' Perspective - Piippo, Noora (2021)
This research explores the effectiveness of ethics and compliance work in the Nordics from a compliance officer’s perspective. In this thesis, ethics and compliance work means the systematic implementation of ethics and compliance programs and associated guidelines. Nordic perspective is chosen because even though the Nordic countries have low corruption rates, business scandals do emerge all the time in different fields. Getting a better understanding of ethics and compliance work can help organizations prevent these scandals and compliance officers’ perspective is important as they not only know ethics but also have a practical perspective. The research topic is approached by four questions that emphasize different aspects of effectiveness ethics and compliance work. The questions are about measuring the effectiveness of ethics and compliance work, the impact of ethics and compliance on organizations’ culture, the best ways to reduce unethical conduct, and the activities that compliance officers that have not been able to implement. These research questions construct the overall picture of ethics and compliance work and increase the understanding of the effectiveness of the work. The theoretical framework consists of previous studies and theories around ethics and compliance work, the impact of ethics and compliance work, and Kaptein’s (2017) struggle theory. The research was conducted as a survey and in cooperation with the Nordic Business Ethics initiative. The data were analyzed by using both quantitative and qualitative methods. The data consisted of 122 responses from Finland, Sweden, Norway, Denmark, and Iceland. The results show that many compliance officers in the Nordic countries measure ethics and compliance work effectiveness in a variety of ways but there are also organizations that do not measure the effectiveness of ethics and compliance work at all. Compliance officers see that the work has a positive impact on the organization's culture and more implications for the future than for the present. ...